Effect of plasma MicroRNA on antihypertensive response to beta blockers in the Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) studies - Solayman, Mohamed H.; Langaee, Taimour Y.; Gong, Yan; Shahin, Mohamed H.; Turner, Stephen T.; Chapman, Arlene B.; Gums, John G.; Boerwinkle, Eric; Beitelshees, Amber L.; El-Hamamsy, Manal; El-Wakeel, Lamia; Cooper-DeHoff, Rhonda M.; et al. (European journal of pharmaceutical sciences, 2019)
β-blockers show variable efficacy as antihypertensives. Herein, we evaluated plasma miRNAs as biomarkers for defining antihypertensive response to β-blockers. Expression of 22 β-blocker pharmacodynamics-related miRNAs was assessed in baseline plasma samples from 30 responders and 30 non-responders to metoprolol from the PEAR-2 study (Discovery). Logistic regression was performed to identify miRNAs significantly associated with metoprolol response. Those miRNAs were profiled in baseline plasma samples from 25 responders and 25 non-responders to atenolol from the PEAR study (validation). In discovery, miR-101, miR-27a, miR-22, miR-19a, and let-7e were significantly associated with metoprolol response (P = 0.01, 0.017, 0.025, 0.025, and 0.04, respectively). In validation, miR-19a was significantly associated with atenolol response (P = 0.038). Meta-analysis between PEAR-2 and PEAR revealed significant association between miR-19a (P = 0.004), miR-101 (P = 0.006), and let-7e (P = 0.012) and β-blocker response. Hence, miR-19a, miR-101, and let-7e, which regulate β1-adrenergic receptor and other β-blocker pharmacodynamics-related genes, may be biomarkers for antihypertensive response to β-blockers. [Display omitted]